IMPLEMENTASI MODEL “PjBL-STEM” BERBASIS KOMUNITAS UNTUK MENINGKATKAN KETERAMPILAN MENULIS GURU: KOLABORASI DENGAN KKG MUFAKAT DESA PUNDU - Misrita, Misrita; Agung Wibowo; Imam Qalyubi; Nguyen Thanh Tuan; Lia Agustina; Nazar Hasby (Bajang Institute, 2025)
This study implements a community-oriented STEM-based Project-Based Learning (PjBL-STEM) model to improve English writing skills among elementary school teachers in Pundu Village, Cempaga Hulu Subdistrict, East Kotawaringin Regency. The background of this study stems from the low writing culture among teachers, limited access to literacy training, and the lack of systematic documentation of innovative learning practices in the Mufakat KKG environment. This program aims to strengthen reflective and scientific writing competencies, increase awareness of literacy based on local environmental issues, and produce educational outputs in the form of digital modules, scientific articles, and video documentation. The research method uses a project-based community service design carried out over five months through three main stages: preparation, training, and mentoring. The subjects of the activity were 20 teachers who were members of the KKG. The training included an introduction to the PjBL-STEM concept, reflective writing practice, the preparation of learning modules, and the implementation of a school waste management project. Data was obtained through observation, participatory evaluation, analysis of written products, and partner feedback. The results showed that participants experienced a significant increase in their ability to compose argumentative paragraphs, design learning projects, and systematically document teaching practices. Three project-based thematic learning modules were successfully produced, accompanied by a four-minute documentary video and a draft scientific article ready for publication. The program also encouraged a change in the literacy culture at KKG through continuous collaboration and the implementation of waste management practices at school. It was concluded that the PjBL-STEM model was effective in strengthening teachers' professional literacy, enhancing pedagogical creativity, and was relevant for application in a rural context. In the future, the sustainability of the program is recommended through continued mentoring and facilitation of the publication of teachers' scientific works